A arte narrativa como experiência do ensino de Filosofia no nível médio. - DEUS, Danillo Matos de (2019)
This research aims to analyze the proposal of the use of narrative art as a methodological resource capable of providing critical-reflexive philosophical teaching at the middle level at CETI Domingos Vieira Filho. This resource can be used by teachers in the classroom, and can serve as a facilitating tool for students to learn in basic education. It is observed that the initiation of young people in a common and public world requires that educators take the authority to position themselves before the learners, using methodological strategies that bring them closer to the traditional knowledge inherited from our ancestors. The student is a being in the world who experiences a constant process of composition of his own knowledge. We can then say that it is essential that the teacher seeks to transmit the cultural knowledge that constitutes the human tradition so that the young can constitute their learning. For Hannah Arendt, education has the task of introducing the world to newcomers and forming an identity of preservation and renewal; otherwise, when responsibility for the world is not assumed by adults, public space deteriorates, causing their address is in danger In this sense, it is necessary to ask: is it possible to educate newcomers with responsibility and to insert them into the public sphere, using the art of narrating as a methodological resource for the teaching of philosophy. Based on the above question, we have as general objective the analysis of the proposal of the use of narrative as a methodological resource capable of providing critical-reflexive philosophical teaching at the middle level at CETI Domingos Vieira Filho. The following specific objectives are: to investigate the methodology of teaching philosophy; describe the implications for the methodology of philosophy teaching in the light of Hannah Arendt's thinking: the concept of tradition; to evaluate the art of narrating as a motivating methodology for students' access to the treasure of tradition.